1997
DOI: 10.3109/10428199709058338
|View full text |Cite
|
Sign up to set email alerts
|

Early High Dose Chemotherapy Intensification with Autologous Bone Marrow Transplantation in Lymphoma Associated with Retention of Fertility and Normal Pregnancies in Females

Abstract: As more centres consider autologous bone marrow and peripheral blood stem cell transplantation for patients with high risk Hodgkin's disease (HD) and non-Hodgkin's lymphoma (NHL) in first complete remission (CR1) the long term sequelae of such treatments have to be considered. One of the most important side effects of such intensive treatment is loss of fertility. Sperm banking before treatment commences is available for males but unfortunately cryopreservation of ova/ovarian tissue is not yet possible for fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…6 Successful pregnancies in women after SCT are well documented. 3,23,24 Similarly, a recent study showed that 85% of pregnancies after SCT resulted in live births. 21 A large cohort study by Sanders et al 4 showed that out of 708 post-pubertal women, 110 resumed normal ovarian function, of which only 32 subsequently became pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…6 Successful pregnancies in women after SCT are well documented. 3,23,24 Similarly, a recent study showed that 85% of pregnancies after SCT resulted in live births. 21 A large cohort study by Sanders et al 4 showed that out of 708 post-pubertal women, 110 resumed normal ovarian function, of which only 32 subsequently became pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…138 Melphalan alone or associated with VP16 or cyclophosphamide in SCT conditioning is compatible with return of fertility in up to 50% of cases. 141,146 Fewer studies have evaluated gonadal function following autologous SCT, and most of these studies have involved small numbers of patients. The use of BEAM (bischolorethylnitrosourea, etoposide, ara-C, melphalan) conditioning for autografts may be associated with a high incidence of gonadal recovery in women, 147 but in men azoospermia is almost always the rule.…”
Section: Fertility Following Sct For Nonmalignant Diseasementioning
confidence: 99%
“…3,4 The risk of gonadal damage is higher with increasing doses of alkylating agents, total body irradiation (TBI), and older age in women at the time of transplant. 5 Although successful pregnancies after HCT have been reported previously, [6][7][8][9][10][11] the evidence suggests that female survivors may be at an increased risk of spontaneous abortions and miscarriages, pre-term delivery and low birth weight babies. 12,13 To further investigate pregnancy outcomes and describe the magnitude of compromise in reproductive function, as indicated by prevalence of selfreported pregnancy occurrence and pregnancy outcomes, we utilized the cohort of survivors participating in the Bone Marrow Transplant Survivor Study (BMTSS) and compared their experience with a sibling comparison group.…”
Section: Introductionmentioning
confidence: 99%